PENURUNAN KADAR SIANIDA SINGKONG PAHIT PADA PROSES FERMENTASI CAIR BAKTERI BREVIBACTERIUM LACTOFERMENTEMUM BL-1M76 - Purawisastra, Suryana; Yuniati, Heru (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
THE REDUCTION OF THE CYANIDE CONTENT OF BITIER CASSAVA BY THE PROCESS OF LIQUID FERMENTATION USING BREVIBACTERIUM LACTOFERMENTUM BL-1M76. Background: Cassava is one of the important source of carbohydrate in tropical countries, that easliy grows in any kind of soil. However, there is a kind of cassava containing cyanide substance, which is toxic for human consumption. This kind of cassava known as bitter cassava contains more starch, but it can't be used as food directly. Usually, people uses this cassava as raw material for producing starch known as 'tapioka' by the traditional method. The cyanide substance in cassava can be degraded by bacteria known as Brevibacterium sp R312 that is capable to degrade about 80% of the cyianide content in cassava, since this bacteria produces some enzymes namely E glucosidase, nitrilhydratase, and amidase, which degrade this cyanide substance. In our laboratory, has another strain of this bacteria, Brevibacterium fermentum BL-1M76, which Is not harmful and has potential capability in producing amino acid of lysine. Objectives: The study was conducted to investigate the potential of the bacteria Brevibacterium fermentum BL-1M76 in reducting of the cyanide substance of bitter cassava using the process of liquid fermentation. Materials and Methods: This experiment used four kinds of bitter cassava obtained from the Balai Penelitian Bioteknologi Tanaman Pangan, Departemen Pertanian (The Research Station of Biotechnology for Food Crops). Those cassavas are known as Adira II, Adria IV, 39.1.1 code, and 46.8 code. The liquid fermentation was conducted in the erlenmeyer flask 250 ml containing 10 ml of 10% cassava medium. The process of fermentation was done in two steps. The first step was to decide the maxmium volume and concentration cell of bacteria suspension, and the duration time of the incubation at the 28°C. The observation was done to the changes content of cyanide, and protein of the cassava medium due to the fermentation. Results: The maximum volume of bacteria cell in the first fermentation was 5 ml for 10 ml of 10% cassava medium. In the second fermentation indicated that the achievement degradation of Brevibacterium fermentum BL-1M76 cyanide substances for all kind bitter cassava was 100%. However, the protein content was not shown any different. Conclusions: The cyanide substance contained in bitter cassava known as Adira II, Adira IV, 39.1.1 code, and 46.8 code can be degraded by the bacteria of Brevibacterium fermentum BL-1M76 in the process of liquid fermentation. Keywords: cyanide, brevibacterium fermentum, bitter cassava, liquid fermentation